Addressing Medical Deserts in Europe: Lessons From a Comparative Analysis - Domagała, Alicja; Dubas‐Jakóbczyk, Katarzyna; Gonzalez, Ana Isabel Gonzalez; Likic, Robert; Michalska, Kamila; Kowalska‐Bobko, Iwona; Sowada, Christoph; Flinterman, Linda; Dan, Sorin; Batenburg, Ronald (John Wiley & Sons, 2026)
Background European countries face a common problem of medical deserts—areas where the population has limited access to healthcare services. Objective This article aims to define medical deserts and provide an in-depth overview of the factors driving desertification and the solutions applied to reduce its negative consequences across six European countries: the Netherlands, Spain, Poland, Croatia, Germany and Ireland. Methods Applied methods include five consecutive steps: (1) development of a case study template; (2) defining criteria and selecting case study countries, (3) desk research, (4) consultation with national experts and (5) comparative analysis. Results There is no formally recognised definition of medical deserts in all the analysed countries. Nevertheless, the concept is often associated with sparsely populated, isolated areas with limited access to healthcare services. The factors driving desertification are similar across the six countries and include: ageing and depopulation, health workforce deficits, unattractive working conditions and geographical factors. Solutions implemented to mitigate the negative effects of medical deserts can be classified into several broad categories: health workforce planning and monitoring, training and career pathways, innovative healthcare models, support mechanisms and infrastructure development. Conclusions The factors driving medical deserts in European countries are complex and multidimensional. In consequence, the policy approaches aimed at limiting their negative consequences also require a comprehensive approach. Addressing medical deserts requires focusing on both the supply and demand sides of health services provision and comprehensive strategies tailored to each country's or region's specific circumstances. Patient or Public Contribution This study was conducted within the ROUTE-HWF project framework, which emphasised the importance of patient and public involvement throughout the research process. Their contribution was particularly valuable during national and international workshops with key stakeholders, including community representatives, healthcare professionals and policymakers. These stakeholder workshops focused on discussing the root causes of medical deserts and exploring national and regional strategies to address them. This inclusive approach ensured that the analysis of the factors driving desertification and potential solutions incorporated the perspectives and lived experiences of affected populations.
Keywords: Health workforce shortages; medical deserts; recruitment and retention of health workers; regional health policies; fi=Julkisjohtaminen|en=Public Management|